2012
DOI: 10.1021/nn300726r
|View full text |Cite
|
Sign up to set email alerts
|

Edge Structural Stability and Kinetics of Graphene Chemical Vapor Deposition Growth

Abstract: The energetics and growth kinetics of graphene edges during CVD growth on Cu(111) and other catalyst surfaces are explored by density functional theory (DFT) calculations. Different from graphene edges in vacuum, the reconstructions of both armchair (AC) and zigzag (ZZ) edges are energetically less stable because of the passivation of the edges by the catalytic surface. Furthermore, we predicated that, on the most used Cu(111) catalytic surface, each AC-like site on the edge is intended to be passivated by a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
209
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 190 publications
(228 citation statements)
references
References 43 publications
14
209
2
3
Order By: Relevance
“…The zigzag oriented smooth edges in moderate H 2 plasma can serve as the active sites for the crystal growth of graphene in the CH 4 /H 2 plasma. After growth, the zigzag configurations transform into armchair configurations, which is in agreement with previous theoretical studies,102, 103 as shown in Figure 14c. In order to reveal the critical crystal growth mechanism in atomic scale, scan tunneling microscopy (STM) studies are performed to characterize the edge structures.…”
Section: Mechanism Of Graphene Growth By Pecvdsupporting
confidence: 92%
“…The zigzag oriented smooth edges in moderate H 2 plasma can serve as the active sites for the crystal growth of graphene in the CH 4 /H 2 plasma. After growth, the zigzag configurations transform into armchair configurations, which is in agreement with previous theoretical studies,102, 103 as shown in Figure 14c. In order to reveal the critical crystal growth mechanism in atomic scale, scan tunneling microscopy (STM) studies are performed to characterize the edge structures.…”
Section: Mechanism Of Graphene Growth By Pecvdsupporting
confidence: 92%
“…In a similar attempt to explain observations of the predominantly ZZ edges observed in growing isles, Shu et al [345] carried out a comprehensive DFT study ranging from calculating stabilities of several edge terminations on the Cu(111) surface, their ability to incorporate additional C adatoms and the C 2 cluster, and finally estimating the growth rate of different edges and correspondingly the island shapes and their dominant termination during growth. In their calculations they attached either a ZZ or AC graphene nanoribbon (GNR) to a step on the metal surface, in a similar fashion to the study in [346].…”
Section: Atomistic Attachment Processesmentioning
confidence: 99%
“…Therefore, the kink sites are the most active for carbon addition or removal onto/from a graphene edge. If the graphene growth is attachment limited and all possibilities for carbon addition/removal onto/from an arbitrary graphene edge with a slanted angle θ are considered, then a simplified formula for the edge orientation-dependent growth/etching rate is (19,21,23,24) RðθÞ ≈ n ZZ ðθÞ p expð−E ZZ =kTÞ + n AC ðθÞexpð−E AC =kTÞ + n K ðθÞ; [2] where n ZZ (θ), n AC (θ), and n K (θ) are the concentrations of the ZZ sites, the AC sites, and the kinks, respectively, along the edge. The calculated formation energies of the ZZ and AC nuclei on a Pt(111) surface are 2.24 eV and 1.60 eV, respectively ( Fig.…”
Section: Significancementioning
confidence: 99%
“…The edge structure of graphene has been shown to significantly influence its various fundamental properties, such as its electronic and magnetic properties, its edge stability, and its chemical reactivity (14)(15)(16)(17)(18). Similarly, the graphene edges, as the sites at which carbon accretion to the twodimensional honeycomb lattice occurs, likely influence the graphene growth (19)(20)(21).…”
mentioning
confidence: 99%